Anonymity - Macrina, Alison; Cooper, Talya (Library futures, 2019)
This book explores the roles and ramifications of anonymity. In the virtual realm, anonymity means that such bedrock values of librarianship as privacy, free speech, and intellectual freedom coexist uneasily with the proliferation of fake news, sexist and racist sentiments, and repugnant ideologies. The book covers apps and forums that promote anonymity as a central feature, and how anonymous content has become valuable fodder for news organizations and clickbait websites.